Thermostable lipase from Pichia sp. strain RT: identification, production and characterization - Mahyon, Nur Iznida; Zulkifli, Nurul Izzati; Mustaffa Kamal, Nurfarahain; Salleh, Abu Bakar; Oslan, Siti Nurbaya (Malaysian Society for Molecular Biology and Biotechnology, 2018)
Lipases are hydrolytic enzymes that have been widely used in industries. In order to meet the industrial demands, thermostable lipases which can withstand high temperatures are required. We sought to optimize the lipase production and to characterize the crude lipase from a locally isolated yeast. Yeast from rotten tomato (from Selangor, Malaysia) which has been identified Pichia sp. strain RT and was found to have thermostable lipase. The morphological features of the isolate were analyzed using SEM and TEM. The microscopy examination confirmed that strain RT was a yeast species. Amplification of lipase gene from cDNA library of the Pichia sp. strain RT showed the gene possessed 100% similarity to the hypothetical protein of Meyerozyma guilliermondii ATCC6260. In addition, the yeast achieved the maximum lipase activity at 30°C with 200 rpm after 72 hours of cultivation. The lipase has the optimum temperature at 75°C and retained nearly 50% of residual activity after 30 minutes of pre-incubation at 75°C. The optimal pH for RT lipase was at pH 9 and it highly stable within pH range 7–10. Physical parameters and the characteristics of crude lipase in strain RT have been successfully investigated. This finding has given an insight for the use of newly isolated thermostable lipase for industrial applications.